Detección mejorada de la microsismicidad y evaluación de detonantes dinámicos en la cuenca central del Mar de Mármara, Turquía (2020)
This project presents an improved detection of microseismicity for the sea of Marmara central basin, an inland sea at Europe South-East, in Turkey, which is under the effect of North Anatolian Fault. The procedure is applied to the continuous records between 25 and 31 August 2011, with two principal algorithms. The first one is Subspace Detector, that stands for a Match Filter on a subspace of the total events (main cluster). Also, the Empirical Subspace Detector that uses the singular value decomposition of the subspace, to make the cross correlation with the continuous records. Thus, the algorithms detected 819 real events with a 20% better performance from the Empirical Subspace Detector. This can be explained because this method is more favorable in dense and clustered distributions, such as the one we found between 27.85°-28° longitude and 5-15 km depth of the sea of Marmara central basin...